Nuclear translocation of RELB is increased in diseased human liver and promotes ductular reaction and biliary fibrosis in mice - Elßner, Christin; Goeppert, Benjamin; Longerich, Thomas; Scherr, Anna-Lena; Rupp, Christian; Kather, Jakob Nikolas; Kautz, Nicole; Breuhahn, Kai; Gdynia, Georg; Rössler, Stephanie; Schirmacher, Peter; Jäger, Dirk; et al. (Gastroenterology, 2019)
Background & Aims - Cholangiocyte proliferation and ductular reaction contribute to the onset and progression of liver diseases. Little is known about the role of the transcription factor nuclear factor-κB (NF-κB) in this process. We investigated the activities of the RELB proto-oncogene NF-κB subunit in human cholangiocytes and in mouse models of liver disease characterized by a ductular reaction. - Methods - We obtained liver tissue samples from patients with primary sclerosing cholangitis, primary biliary cholangitis, hepatitis B or C virus infection, autoimmune hepatitis, alcoholic liver disease, or without these diseases (controls) from a tissue bank in Germany. Tissues were analyzed by immunohistochemistry for levels of RELB and lymphotoxin β (LTB). We studied mice with liver parenchymal cell (LPC)-specific disruption of the cylindromatosis (CYLD) lysine 63 deubiquitinase gene (Cyld), with or without disruption of Relb (CyldΔLPC mice and Cyld/RelbΔLPC mice) and compared them with C57BL/6 mice (controls). Mice were fed 5-diethoxycarbonyl-1,4-dihydrocollidine (DDC) or standard chow diets to induce biliary injury or were given injections of CCl4 to induce non-cholestatic liver fibrosis. Liver tissues were analyzed by histology, immunohistochemistry, immunoblots, in situ hybridization, and quantitative real-time polymerase chain reaction. Cholangiocytes were isolated from normal human liver, incubated with LTB receptor agonist, and transfected with small interfering RNAs to knock down RELB. - Results - In liver tissues from patients with primary sclerosing cholangitis, primary biliary cholangitis, chronic infection with hepatitis B or C virus, autoimmune hepatitis, or alcoholic liver disease, we detected increased nuclear translocation of RELB and increased levels of LTB in cholangiocytes that formed reactive bile ducts compared with control liver tissues. Human cholangiocytes, but not those with RELB knockdown, proliferated with exposure to LTB. The phenotype of CyldΔLPC mice, which included ductular reaction, oval cell activation, and biliary fibrosis, was completely lost from Cyld/RelbΔLPC mice. Compared with livers from control mice, livers from CyldΔLPC mice (but not Cyld/RelbΔLPC mice) had increased levels of mRNAs encoding cytokines (LTB; CD40; and tumor necrosis factor superfamily [TNFSF] members TNFSF11 [RANKL], TNFSF13B [BAFF], and TNFSF14 [LIGHT]) produced by reactive cholangiocytes. However, these strains of mice developed similar levels of liver fibrosis in response to CCl4 exposure. CyldΔLPC mice and Cyld/RelbΔLPC mice had improved liver function on the DDC diet compared with control mice fed the DDC diet. - Conclusion - Reactive bile ducts in patients with chronic liver diseases have increased levels of LTB and nuclear translocation of RELB. RELB is required for the ductular reaction and development of biliary fibrosis in CyldΔLPC mice. Deletion of RELB and CYLD from LPCs protects mice from DDC-induced cholestatic liver fibrosis.